Comprehensive Advanced Physicochemical Characterization and In Vitro Human Cell Culture Assessment of BMS-202: A Novel Inhibitor of Programmed Cell Death Ligand - Hasham Shafi; Andrea J. Lora; Haley M. Donow; Sally E. Dickinson; Georg T. Wondrak; H.-H. Sherry Chow; Clara Curiel-Lewandrowski; Heidi M. Mansour (Pharmaceutics)
Background/Objectives: BMS-202, is a potent small molecule with demonstrated antitumor activity. The study aimed to comprehensively characterize the physical and chemical properties of BMS-202 and evaluate its suitability for topical formulation, focusing on uniformity, stability and safety profiles. Methods: A range of analytical techniques were employed to characterize BMS-202. Scanning Electron Microscopy (SEM) was used to assess morphology, Differential Scanning Calorimetry (DSC) provided insights of thermal behavior, and Hot-Stage Microscopy (HSM) corroborated these thermal behaviors. Molecular fingerprinting was conducted using Raman spectroscopy and Fourier Transform Infrared (FTIR) spectroscopy, with chemical uniformity of the batch further validated by mapping through FTIR and Raman microscopies. The residual water content was measured using Karl Fisher Coulometric titration, and vapor sorption isotherms examined moisture uptake across varying relative humidity levels. In vitro safety assessments involved testing with skin epithelial cell lines, such as HaCaT and NHEK, and Transepithelial Electrical Resistance (TEER) to evaluate barrier integrity. Results: SEM revealed a distinctive needle-like morphology, while DSC indicated a sharp melting point at 110.90 ± 0.54 ℃ with a high enthalpy of 84.41 ± 0.38 J/g. HSM confirmed the crystalline-to-amorphous transition at the melting point. Raman and FTIR spectroscopy, alongside chemical imaging, confirmed chemical uniformity as well as validated the batch consistency. A residual water content of 2.76 ± 1.37 % (w/w) and minimal moisture uptake across relative humidity levels demonstrated its low hygroscopicity and suitability for topical formulations. Cytotoxicity testing showed dose-dependent reduction in skin epithelial cell viability at high concentrations (100 µM and 500 µM), with lower doses (0.1 µM to 10 µM) demonstrating acceptable safety. TEER studies indicated that BMS-202 does not disrupt the HaCaT cell barrier function. Conclusions: The findings from this study establish that BMS-202 has promising physicochemical and in vitro characteristics at therapeutic concentrations for topical applications, providing a foundation for future formulation development focused on skin-related cancers or localized immune modulation.